Measurement of the decay B-→D*0e-ν̄e - Aubert, B; Bona, M; Karyotakis, Y; Lees, J; Poireau, V; Prudent, X; Tisserand, V; Zghiche, A; Tico, J; Grauges, E; Lopez, L; Palano, A; et al. (2008)
Using 226×106 BB̄ events recorded on the Υ(4S) resonance with the BABAR detector at the SLAC e+e- PEP-II storage rings, we reconstruct B-→D*0e-ν̄e decays using the decay chain D*0→D0π0 and D0→K-π+. From the dependence of their differential rate on w, the dot product of the four velocities of B- and D*0, and using the form factor description by Caprini et al. with the parameters F(1) and ρA12, we obtain the results ρA12=1.16±0. 06±0.08, F(1)|Vcb|=(35.9±0.6±1.4)×10-3, and B(B-→D*0e-ν̄e)=(5.56±0.08±0.41)%. © 2008 The American Physical Society.